2015
DOI: 10.1016/j.bjp.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The influence of leaf age on methylxanthines, total phenolic content, and free radical scavenging capacity of Ilex paraguariensis aqueous extracts

Abstract: Please cite this article in press as: Blum-Silva, C.H., et al. The influence of leaf age on methylxanthines, total phenolic content, and free radical scavenging capacity of Ilex paraguariensis aqueous extracts. Revista Brasileira de Farmacognosia (2015), http://dx.BJP 84 1-6 Revista Brasileira de Farmacognosia xxx (2015) xxx-xxx w w w . s b f g n o s i a . o r g . b r / r e v i s t a Original Article a b s t r a c tYerba-mate (Ilex paraguariensis A. St. Hil., Aquifoliaceae) is a South American native species t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 48 publications
1
33
1
5
Order By: Relevance
“…Several authors evaluated the antioxidant activity of I. paraguariensis extracts (de Mejía et al, 2010;Peres et al, 2013;Blum-Silva et al, 2015), though they have used different methods or expressed their results in distinct units, making it impossible to compare them with our results. Berté et al (2011) reported a much lower DPPH scavenging activity for an aqueous spray-dried extract of yerba mate from Brazil (EC 50 value 2520 µg/mL) than the one determined herein.…”
Section: Bioactivity Of the I Paraguariensis Extractsmentioning
confidence: 47%
See 1 more Smart Citation
“…Several authors evaluated the antioxidant activity of I. paraguariensis extracts (de Mejía et al, 2010;Peres et al, 2013;Blum-Silva et al, 2015), though they have used different methods or expressed their results in distinct units, making it impossible to compare them with our results. Berté et al (2011) reported a much lower DPPH scavenging activity for an aqueous spray-dried extract of yerba mate from Brazil (EC 50 value 2520 µg/mL) than the one determined herein.…”
Section: Bioactivity Of the I Paraguariensis Extractsmentioning
confidence: 47%
“…Furthermore, the antioxidant (de Mejía, Song, Heck, & Ramirez-Mares, 2010;Peres, Tonin, Tavares & Rodriguez-Amaya, 2013;Blum-Silva, Chaves, Schenkel, Coelho & Reginatto, 2015;Boaventura et al, 2015b) and anti-inflammatory (Tsai, Tsai, Wuc, Tseng & Tsai, 2010;Arçari et al, 2011, Lanzetti et al, 2012 properties of aqueous yerba mate extracts have been extensively investigated. However, studies on the cytotoxic potential of I.…”
Section: Introductionmentioning
confidence: 99%
“…These programs aim at selecting genotypes with additional adaptive traits to environmental cultivation conditions, high-leaf mass production, and tolerance to biotic and abiotic factors. Recently, emphasis has been placed on the inclusion traits linked to the content of some relevant chemical compounds that can directly affect the quality of commercial products and on their biological effects (Morais et al, 2009;González de Mejía et al, 2010;Sturion & Resende, 2010;Anesini et al, 2012;Barbosa et al, 2015;Blum-Silva et al, 2015;González Arbeláez et al, 2016;Cardozo Junior & Morand, 2016). However, increasing productivity is always desirable for breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…According to Dartora et al [27], yerba-mate directly exposed to sunlight has higher levels of phenolic compounds as compared with the shaded plant. Blum-Silva et al [28] reported that the concentration of phenolic compounds is higher in younger leaves. However, Strassmann et al [29] found greater concentration of total phenolic compounds in aqueous extracts of cultivated yerba-mate leaves, either young or adult (149.68 and 135.40 µg/mL, respectively) in comparison to native leaves (64.08 µg/mL and 59.30 µg/mL, respectively).…”
Section: Polyphenol Content and Antioxidant Activitymentioning
confidence: 98%